PEMBUATAN BAHAN AJAR INTERAKTIF BERMUATAN KARAKTER DENGAN PENDEKATAN SAINTIFIK PADA MATERI FLUIDA STATIK DAN DINAMIK FISIKA SMA KELAS XI - Frima Suci Agustia; Yenni Darvina; Yurnetti Yurnetti (PILLAR OF PHYSICS EDUCATION, 2017)
Learning demanded by the of 2013 curriculum is learning to student-centered, interactive, multimedia-based, and use the scientific approach. In addition, the 2013 curriculum teachers are required provide character education to students. One of the factors supporting the creation of learning is learning resource. Learning resources is expected to help the learning process and facilitate the learners’ needs such as the learning style. These learning resources are in the form of teaching materials, handouts, modules, and worksheets. However, the teaching materials used by teachers do not correspond to the demands of the 2013 curriculum and has not met the learners’ needs. Teaching materials are used in the form of printed teaching materials that have not been based on multimedia. Instructional materials are still a bit implicitly contains character values. LKS used to load materials and evaluation questions not contain simple experiments using the scientific approach. Therefore, the need to design interactive teaching materials charged character with a scientific approach. This study aims to produce products such as interactive teaching materials charged character with the scientific approach to the static and dynamic fluid material valid.This research is the development (research and development) using 4-D model of development which is reduced to 3-D with the definition phase (define), design (design), and development (develop). Subjects were 5 people validator ie 3 people physics professor FMIPA UNP and 2 physics teachers SMAN 6 Padang. Data were analyzed with descriptive analysis techniques.Teaching materials include text, sound, animation, music, and video. Teaching materials containing character values and scientific approach. Based on research that has been done, has produced products such as interactive teaching materials charged character with a scientific approach. Products are categorized valid study of aspects of material substance with an average value of 88%, appearance (visual communication) with an average value of 88.6%, the design of teaching materials with an average value of 89.7%, and the use of software to the average value -rata 93.3%.